Teaching Justice after MacIntyre: Toward a Catholic Philosophy of Moral Education - Bergman, Roger (Catholic Education: A Journal of Inquiry and Practice, 2008)
How is the commitment to social justice sustained over a lifetime? This would seem to be a matter of character, and that calls attention to the Aristotelian tradition in ethics. No one provides as much insight into the challenge of the contemporary appropriation of this tradition as Alasdair MacIntyre. Although a moral philosopher rather than a moral educator, MacIntyre’s critique of the failure of the Enlightenment project to construct a rationally based universal ethic, coupled with a critique of the modern nation-state of liberal capitalism as antithetical to the practice of virtue for the common good, provides a challenging if controversial context in which moral educators might think about justice pedagogy today.